Human resource management and developing proactive environmental strategies: The influence of environmental training and organizational learning - Vidal‐Salazar, María Dolores; Cordón‐Pozo, Eulogio; Ferrón‐Vilchez, Vera (Human Resource Management, 2012)
AbstractThe need to implement advanced approaches to protect the environment is forcing companies to refocus their internal procedures and actions. To match employees' capabilities and the organization itself to these new requirements, the human resource management department can offer some key tools. This article analyzes whether environmental training (ET) and organizational learning (OL) positively influence the development of proactive environmental strategies (PESs) and compares the two processes, which differ in the time, costs, and difficulty required to implement them. Companies in the tourism sector are currently facing a highly dynamic environment where innovativeness is a decisive factor for achieving competitiveness. As such, we analyze whether the presence or absence of innovativeness influences the development of these two mechanisms. Using a sample of 252 tourism companies, we tested these relationships using structural equation modeling. The findings showed that (1) innovativeness is an antecedent of implementing ET and OL in the companies sampled, (2) both mechanisms promote implementing PESs, and (3) ET is equally as effective as OL for this purpose. Managers should take these findings into account when deciding which mechanism to apply when striving to achieve environmental proactivity.